2019
DOI: 10.1126/science.aav7932
|View full text |Cite
|
Sign up to set email alerts
|

Exotic states in a simple network of nanoelectromechanical oscillators

Abstract: Synchronization of oscillators, a phenomenon found in a wide variety of natural and engineered systems, is typically understood through a reduction to a first-order phase model with simplified dynamics. Here, by exploiting the precision and flexibility of nanoelectromechanical systems, we examined the dynamics of a ring of quasi-sinusoidal oscillators at and beyond first order. Beyond first order, we found exotic states of synchronization with highly complex dynamics, including weak chimeras, decoupled states,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(138 citation statements)
references
References 64 publications
2
128
0
Order By: Relevance
“…In summary, in this work we achieve second-and thirdorder phase reductions of the MF-CGLE. In our view, higherorder phase reductions promise to be crucial for our understanding of collective chaos and other exotic phenomena [12]. Moreover, analytic higher-order phase reductions may also serve as test beds for numerical phase reductions recently implemented [63].…”
Section: E Conclusionmentioning
confidence: 98%
See 3 more Smart Citations
“…In summary, in this work we achieve second-and thirdorder phase reductions of the MF-CGLE. In our view, higherorder phase reductions promise to be crucial for our understanding of collective chaos and other exotic phenomena [12]. Moreover, analytic higher-order phase reductions may also serve as test beds for numerical phase reductions recently implemented [63].…”
Section: E Conclusionmentioning
confidence: 98%
“…which can be inserted in (12) to obtain the ǫ 2 contribution. Through elementary manipulations the second-order phase reduction of Eq.…”
Section: B Isochron-based Phase Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent progress in experimental studies has revealed that synchronization can take place in coupled nonlinear oscillators with intrinsically quantum-mechanical origins, such as micro and nanomechanical oscillators [16][17][18][19][20], spin torque oscillators [21], and cooled atomic ensembles [22,23]. Moreover, theoretical studies have been performed on the synchronization of nonlinear oscillators which explicitly show quantum signatures , such as optomechanical oscillators [24][25][26], cooled atomic ensembles [27,28], trapped ions [29][30][31], spins [32], and superconducting circuits [33].…”
Section: Introductionmentioning
confidence: 99%